2023
DOI: 10.1021/acsomega.3c00816
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Carbon Materials as Electrodes for High-Performance Supercapacitors: From Marine Biowaste to High Specific Surface Area Porous Biocarbons

Abstract: Waste, in particular, biowaste, can be a valuable source of novel carbon materials. Renewable carbon materials, such as biomass-derived carbons, have gained significant attention recently as potential electrode materials for various electrochemical devices, including batteries and supercapacitors. The importance of renewable carbon materials as electrodes can be attributed to their sustainability, low cost, high purity, high surface area, and tailored properties. Fish waste recovered from the fish processing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Additionally, the pores can provide additional surface area for charge storage, and facilitate the diffusion of ions into and out of the electrode. Even though, to the best of our knowledge, there are no reports in the literature about the use of organic materials extracted from blue shark discards (gelatine and chondroitin sulfate) for the preparation of carbon electrodes for application in energy storage devices, several marine waste precursors have been used for this application, such as glycogen [11], crab shells [13], fish scales [14][15][16], prawn shells [17], fish bones [18], and squid pens [12]. These studies present higher specific surface areas, pores, and specific capacitances than the present results.…”
Section: Preliminary Results: Ball-milling Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the pores can provide additional surface area for charge storage, and facilitate the diffusion of ions into and out of the electrode. Even though, to the best of our knowledge, there are no reports in the literature about the use of organic materials extracted from blue shark discards (gelatine and chondroitin sulfate) for the preparation of carbon electrodes for application in energy storage devices, several marine waste precursors have been used for this application, such as glycogen [11], crab shells [13], fish scales [14][15][16], prawn shells [17], fish bones [18], and squid pens [12]. These studies present higher specific surface areas, pores, and specific capacitances than the present results.…”
Section: Preliminary Results: Ball-milling Effectmentioning
confidence: 99%
“…High-specific-area materials have a greater surface area per unit mass, allowing them to store and discharge more charge more effectively than low-specific-area materials. Brandão et al [11,12,19] showed that the higher the specific capacitance, the larger the surface area of carbons. An increased surface area can accommodate more electrolyte ions, leading to a more significant amount of stored charge.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…There is no significant buildup of surface films or other changes that could increase the resistance. It also suggests that the material's intrinsic electrical conductivity appears to be durable, maintaining its performance despite prolonged use at high current density, and lastly, it indicates that the contact resistance between the current collector and the active material, as well as any connections within the cell, have not degraded, which could have led to an increase in ESR [45][46][47].…”
Section: Galvanostatic Charge Discharge (Gcd) Analysismentioning
confidence: 99%
“…The following ingredients, hydrolyzed collagen (34 kDa), glycogen (2551 kDa), and hyaluronic acid (51 kDa and 1500 kDa, respectively), were obtained, as indicated in [11,12,43,44], and refrigerated (−20 • C) until use for experiments and the preparation of the cosmetic formulation. Briefly, hydrolyzed collagen was obtained by first treating Prionace glauca skins with 10 volumes of 0.1 M NaOH and stirring in a cold room (4 • C) for 24 h. The liquid was discarded and the NaOH-treated skins washed until neutral pH.…”
Section: Bioactive Compound Ingredientsmentioning
confidence: 99%
“…The obtained acid-soluble collagen was hydrolyzed in a controlled pH-Stat system (Metrohm, Herisau, Switzerland) using papain (Merck, KGAA, Darmstadt, Germany) (E/S: 1/20) for 30 min at 65 • C in a water bath and ultra-filtrated using 30 kDa and 10 kDa Mw cut-off Amicon Ultra Device membranes to achieve the desired molecular weight. Glycogen was isolated from industrial mussel cooking wastewaters after its concentration by ultrafiltration membrane with 100 kDa cut-off (spiral polyethersulfone, 0.56 m 2 , Prep/Scale-TFF, Millipore Corporation, USA), followed by protein precipitation by isoelectric point (pH 4.5) with 5 M HCl, a selective polysaccharide separation using alcoholic precipitation, and finally, an oven-drying step [43]. Hyaluronic acid was produced by fermentation of Streptoccocus zooepidemicus bacterium in low-cost nutritive medium, including tuna viscera peptone [12].…”
Section: Bioactive Compound Ingredientsmentioning
confidence: 99%